Collective Compassion, Digital Sphere and Images of Pathos in the Time of COVID-19 - Gherlone, Laura (Eikón / Imago, 2021)
This article aims to investigate how, during the outbreak of the COVID-19 pandemic, the digital sphere afforded an affective space for the manifestation of collective pain in the face of the death of multitudes of people. A special attention will be given to a series of images viralized by SNSs during February-April 2020 and interpreted in the light of Aby Warburg’s theory of Pathosformeln –images which, through the mediation of the pathetic face, made visible and real the ongoing drama, providing a model of universal expression of compassion–. The article is divided into three parts. First, the idea of “image-centric culture” will be introduced to raise a salient feature of contemporary societies. Second, the topicality of the concept of Pathosformel –originally conceived within the history of art– will be highlighted in order to explain the association between image and emotion that characterizes the present age. Third, the article will provide an interpretation of the images of pathos in the time of COVID-19 through the pathetic expressive formula of the imago pietatis: a visuo-affective model “revived” in contemporaneity and able to universalize and move the interiority of the observer, placing emphasis on empathic pain.